Development of Flipbook Electronic Teaching Materials for Implementing the Scientific Approach in Indonesian Language Learning for Vocational High School Students - Yeni Sulaeman; Ade Hikmat; Wini Tarmini (STAI Hubbulwathan Duri, 2025)
The rapid advancement of information technology has significantly transformed educational practices, particularly in the shift from conventional to digital learning models. In response to this transformation and the implementation of online learning policies by the Ministry of Education and Culture, this study aims to develop electronic teaching materials using a scientific approach for Indonesian language instruction in Class XI of vocational high schools. This research employed a development research design using the 4D model by Thiagarajan, which includes the stages of Define, Design, Develop, and Disseminate. However, the study focused solely on the first three stages due to time and resource constraints. The teaching materials were developed in the form of flipbook-based electronic modules and subjected to expert validation. Three domains were assessed: content (by material experts), language (by linguists), and visual design (by graphic experts). The validation results showed that the electronic flipbook teaching materials achieved an average feasibility score of 83.32%, which falls into the